WHAT DOES THE INTERNET SOUND LIKE? - Bhandari, Aparajita; Bimo, Sara; Butkowski, Chelsea; Noone, Rebecca (AoIR Selected Papers of Internet Research, 2023)
When it comes to the study of internet phenomena, the visual constitutes a privileged mode of analysis, as seen by the ample and storied scholarship on visual media dn visually based methods. In order to disrupt this “hegemony of the visual,” and explore alternate ways of knowing and being online, this panel bring internet studies scholarship into meaningful dialogue with sound studies scholarship and poses the provocation: “how can sound be used methodologically in order to expand and deepen our understanding of the internet?” This topic is addressed in a variety of ways by the contributing authors. The first paper of this panel introduces the concept of deep listening as a feminist analytical method for “tuning-in” to the persistent hegemonic structures that underly digitally mapping technology. The second paper presents the concept of “the sonic interface” as a means to examine how sound mediates our everyday interactions with the internet. The third paper proposes the use of participatory arts based methods as a reflexive and critical framework through which researchers can begin to “listen” to alternative internet narratives while centering the voices of communities rather than researchers. The final paper deploys sound as a method for studying social behaviour on TikTok, and demonstrates the widespread applicability of sonic methods in the wider study of internet phenomena. All in all, this panel aims to highlight the immensely generative potential of centring sound in our interrogations of the online and the digital.